2016
DOI: 10.22456/1679-9216.80955
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Histomorphometry and Evaluation of Ovarian Apoptosis in Queens of Different Age Groups

Abstract: Background: In humans and bitchs the age is another factor that may affect the size of ovarian structures, verifying alterations in the quality of the pool and size of follicular structures, which can compromise the use of these structures for in vitro maturation. There are no reports correlating the morphometric characteristics of the follicles and ovarian apoptosis at different ages in cats. The aim of this study was to evaluate the histomorphometric parameters of follicular growth and the relationship with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This great percentage of primary follicles might be explained by the fact that only young cats were enrolled in the experiments, and, according to Carvalho et al. (), they have a higher amount of primary follicles compared to cats over 6 years of age. Secondary and tertiary follicles accounted for less than 35% of the follicular population, especially in the GC3 and GV3.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This great percentage of primary follicles might be explained by the fact that only young cats were enrolled in the experiments, and, according to Carvalho et al. (), they have a higher amount of primary follicles compared to cats over 6 years of age. Secondary and tertiary follicles accounted for less than 35% of the follicular population, especially in the GC3 and GV3.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the histological evaluation in our study revealed a great frequency of primary follicles in all groups, corroborating the investigation of Carrijo Júnior et al (2010) in cats, Jewgenow and Stolte (1996) in non-domestic felines and Salehnia, Sheikhi, Pourbeiranvand, and Lundgvist (2012) in humans. This great percentage of primary follicles might be explained by the fact that only young cats were enrolled in the experiments, and, according to Carvalho et al (2016), they have a higher amount of primary follicles compared to cats over TA B L E 3 Percentage of apoptotic cells in follicles and stroma in vitrified and control groups evaluated by immunohistochemistry (cleaved caspase-3)…”
Section: Discussionmentioning
confidence: 99%